2009
DOI: 10.1200/jco.2009.22.9773
|View full text |Cite
|
Sign up to set email alerts
|

Underuse of Breast Cancer Adjuvant Treatment: Patient Knowledge, Beliefs, and Medical Mistrust

Abstract: Patient knowledge and beliefs about treatment and medical mistrust are mutable factors associated with underuse of effective adjuvant therapies. Physicians may improve cancer care by ensuring that discussions about adjuvant therapy include a clear presentation of the benefits, not just the risks of treatment, and by addressing patient trust in and concerns about the medical system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
117
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(127 citation statements)
references
References 51 publications
7
117
1
Order By: Relevance
“…Decisions are often time-intensive, complicated, and nuanced, and effective communication is crucial. 30,31 Moreover, such complex care may be particularly challenging for patients with limited social support, superseding life stressors, or medical comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Decisions are often time-intensive, complicated, and nuanced, and effective communication is crucial. 30,31 Moreover, such complex care may be particularly challenging for patients with limited social support, superseding life stressors, or medical comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer care has become increasingly complex, with multiple providers and office visits required to complete recommended adjuvant therapy. Patient factors, such as difficulty accessing care even with insurance, 28 mistrust of the medical system, [28][29][30] and differing preferences may be important. 30,31 Disparities in care are also influenced by the characteristics of physicians 32 and hospitals 33 from which patients obtain care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the decision complexity, communication challenges, patients' heightened emotional state, and time pressure to make a decision, many patients unfortunately make decisions without fully understanding the options and associated risks and benefits [27][28][29]. In some cases, this lack of knowledge can lead to an underuse or overuse of cancer treatments [30,31].…”
Section: The Process Of Shared Decision Making In Oncology Practicementioning
confidence: 99%
“…26,27 For example, studies from European populations have suggested that men of higher education level or from more affluent areas were more likely to seek aggressive treatment for prostate cancer-a behavior that may be driven by trust in providerdelivered therapies and willingness to receive treatment despite potential risks and side effects. 10,28 Schulman et al 29 found that patient race independently influences physician treatment recommendations, with physicians more likely to recommend aggressive therapy for white patients compared with black patients when presented with hypothetical cases of chest pain.…”
Section: Discussionmentioning
confidence: 99%